HIGH INTENSITY INTERVAL TRAINING DOES NOT CHANGE THE AREA IN THE ADIPOCYTES OF THE EPICARDIUM OF FAT RATS - Candido, Fernanda; Costa Gonçalves do Vale;, Daniel; Rodrigues Jimenes, Diogo; Cristina Buttow, Nilza; Patrícia Barbosa, Carmem (Arquivos do Mudi, 2023)
The obesity due to high caloric ingestion is related to the accumulation of body fat and predisposes cardiovascular diseases. Recent studies about the High Intensity Interval Training (HIIT) evidence benefits of its practice in patients that maybe carrying this disease, mainly because of the reduction of comorbidities associated with obesity. This present study has the objective of evaluating the HIIT effects on the adipocytes’ changes of the epicardium adipose tissue in fat animals induced by the consumption of high-fat diet. It was used male rats of Wistar lineage fed daily with HFD and trained by HIIT three times a week for 8 consecutive weeks. The animals were weighted during the training sections and, after its euthanasia, were realized histological analyses of the epicardium adipose tissue. The results showed that HFD increased the body weight of the animals and the side view of the adipocytes. However, the HIIT did not change the area of the adipocytes of the epicardial adipose tissue, even though the diet had been a hypertrophy factor of this tissue. Then, we can conclude that HIIT contributes to avoid the body weight gain but was not capable of reducing the area of the adipocytes of the epicardium adipose tissue.